PEMBERDAYAAN KELOMPOK TANI MELALUI PENYULUHAN BUDIDAYA TANAMAN KAKAO DAN PENGENDALIAN HAMA PENYAKIT KAKAO - Euis Faizatul Muniroh; Gina Safitri; Siti Dilah Fadilah; Sa’diyah Sa’diyah (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2020)
This article aims to identify and analyze the empowerment program for farming groups through countering cultivation and cocoa pest control, and to empower farmer groups by increasing broader insight into the cocoa plant, as well as the pests and diseases that attack these plants. The method of study used Participatory Rural Appraisal (PRA) approach to obtain the local community efforts in conducting their own assessments, analysis and planning. The study results showed that in the last few years, most of the people of Padasuka Village, Sub- District of Petir have planted many cocoa trees. Because it has a normal height of 400 meters above sea level, it makes cacao trees thrive in this village. However, even so, there are still many people who do not really understand how to plant and care for cocoa trees which results in many experiencing crop failures. When viewed in the market, the price of cocoa beans is quite stable so that it can help the community's economy. Therefore, this is inseparable from the role of extension workers who provide education and empowerment of farmers. We together with the Agricultural Extension Center (BPP) have provided education through socialization programs to the community, especially the Harapan Sejahtera III farmer group. Activities carried out include counseling on cocoa cultivation, pest control in cocoa, and field practice of making pest traps.